THE PENAMBAHAN CODMAN PENDULAR EXERCISE PADA PEMBERIAN TERAPI MICRO WAVE DIATHERMY, TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN STRETCHING DAPAT MENINGKATKAN LINGKUP GERAK SENDI ABDUKSI PADA KASUS - Warta, I Nyoman (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 3 (2013): Majalah Ilmiah Fisioterapi Indonesia, 2013)
Range of motion is limited abduction usually occurs in the case of frozen shoulder. This is due to immobilization, resulting in adhesions to the capsule and ligaments that cause decreased tissue elasticity and cause stiffnes. Objective : This research aimed to identifi addition Codman Pendular Exercise on therapy MWD, TENS and stretching to increase range of motion in the case of frozen shoulder abduction.  Method : This research is usingpre test and post test control group design. Patients were randomised into two groups : the Control Group (CG) that use MWD, TENS and stretching is 16 patients. The Experimental Group (EG) that use MWD, TENS, stretching and Codmann Pendular exercise  is 16 patients too. Result : The result of CG test which using compare means with Wilcoxon match pair test, p>0,000 (p=0,000) that mean the intervention in CG is t having significant to increasing range of motion. In the result of EG test which using compare means with paired Wilcoxon match pair test, p<0,05 (p=0,000) that mean the intervention in EG is having significant to increasing range of motion. The result test researcher using compare mean test with Mann-whitney U test, p<0,05 (p=0,000), that means there are significant different between EG result and CG result. In one tail hypothesis got result p<0,05, so it shows that intervention in EG more effective significantly than CG in to increasing range of motion in the case of frozen shoulder abduction. Conclusion : Addition Codman Pendular Exercise on therapy MWD, TENS and stretching to increase range of motion in the case of frozen shoulder abduction.
Keywords: Frozen shoulder, range of motion, Codman pendular exercise.